QUALITY IMPROVEMENT MANAGEMENT BASED ON PARTNERSHIP AND ICT ADVANTAGES (MULTI CASE STUDY AT SMK MUHAMMADIYAH 1 AND SMK YPT 1 PURBALINGGA REGENCY - Nafsir Efendi; Abin Syamsudidin; Iim Wasliman; Daeng Arifin (EARR (Educational Administration Research and Review), 2022)
-